2013
DOI: 10.1007/s00784-013-0986-3
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus reactivation and dental procedures

Abstract: Antiviral prophylaxis for RHL is not routinely recommended for dental procedures, regardless of a prior history of RHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Case reports have also related a herpes simplex virus type 1 infection to severe gingival inflammation and recession after muco‐gingival therapy . Herpes simplex virus type 1 can activate after tooth extraction and has been implicated in ‘dry socket’ pathosis following tooth extraction . Reduced osteogenesis has occurred after transplantation of autologous bone contaminated with Epstein–Barr virus and periodontal bacteria .…”
Section: Disease Associationsmentioning
confidence: 99%
“…Case reports have also related a herpes simplex virus type 1 infection to severe gingival inflammation and recession after muco‐gingival therapy . Herpes simplex virus type 1 can activate after tooth extraction and has been implicated in ‘dry socket’ pathosis following tooth extraction . Reduced osteogenesis has occurred after transplantation of autologous bone contaminated with Epstein–Barr virus and periodontal bacteria .…”
Section: Disease Associationsmentioning
confidence: 99%
“…However, severe RHL after dental treatment was not reported in that study, whereas in our study 45.45% of root canal therapy patients and 27.3% of fixed prosthodontics patients showed RHL after dental treatment. El Hayderi et al suggested that nerve damage due to dental treatment causes HSV-1 reactivation and concluded that oral HSV shedding may be related to invasiveness of dental procedure, but fur- 27 ther studies are needed on this issue (2,37). De Santana Sarmento et al and Caliento et al concluded that kidney transplant recipients (adults and children, respectively) excreted herpes viruses more often than controls, especially HSV-1 and Epstein-Barr virus, with salivary shedding of herpes viruses being more frequent in patients with recent kidney transplantation (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus type 1 (HSV-1) is a member of alpha herpes virus family that is highly infectious (1). HSV-1 is transmitted via oral-oral contact (2) and respiratory secretions (3). It is estimated that the global prevalence of HSV-1 infection in all age group is 67% (3.7 billion people), in eastern meditation countries, this prevalence is 75% (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of these stimuli and how they can act on the viral genome to permit gene expression is not well understood. In the context of human disease, exposure to sunlight, psychological stress, fever, menstruation and surgical resection have all been associated with HSV reactivation (Chida and Mao, 2009; Hayderi et al, 2013; Padgett et al, 1998; Roizman and Whitley, 2013). It is likely that reactivation of HSV in a normal human host results from a combination of factors, including signals that act directly on latently infected neurons and suppression of the immune responses that typically prevent reactivation and clear replicating virus.…”
Section: Triggers Implicated In Hsv Reactivationmentioning
confidence: 99%